Mapping of cisterns and water quality analysis at the Nova Assunção settlement in Aracoiaba, Ceará - Brito, Antônio Patrick Meneses de; Sousa, Manuel Pereira de; Aguiar, Luzia Luziene de Castro; Pinto, Olienaide Ribeiro de Oliveira; Pinto, Ciro de Miranda; Salles, Maria Gorete Flores (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
The work aimed at mapping cisterns and analyzing water quality in the Nova Assunção settlement located in the semi-arid region of Aracoiaba, Ceará. The delimitation of the study area and the manipulation of the cartographic data were performed with the ArcMap 10.3 program. The Global Positioning System (GPS), the Garmim 76scx model, obtained the geographic location of each cistern. A semi-structured questionnaire on the use of water and ways of handling in cisterns was applied in the study area. Six physical- chemical parameters were evaluated in the water: temperature, turbidity, hydrogen ion potential (pH), total dissolved solids (STD), electrical conductivity (EC) and apparent color. Seventeen cisterns were mapped, of which 100% is used for human consumption, 76.5% of which had no protective screen. In the water analysis, inadequacy was observed for the parameters apparent color, EC, turbidity, and pH. In four cisterns, there was 50% irregularity in the attributes. Thus, the mapped cisterns are an an indispensable alternative for the storage and guarantee of water in the settled community, however, some hygiene measures are necessary to improve the use, since the highest destination of water corresponds to human consumption followed by domestic use.